Legitimacy of Travel Prohibition as a Precaution Measure to Prevent the Debtor from Escaping from Justice and Smuggling his Money outside the Kingdom - ALQUDAH, Zakaria Muhammad Falih (Dirasat: Shari’a and Law Sciences, 2020)
This study explains the legitimacy of travel prohibition as a precautionary measure to prevent the debtor from escaping from justice and smuggling his money outside the kingdom as well as Shari’a evidence on that. Furthermore, the study pointed out that travel prohibition is a procedure in the Jordanian Shari’a courts within its jurisdiction in prices, expenses, and travel in custody and the framework of the laws governing this, such as the personal status law, the law of legal proceedings, the law of forensic execution and others. The study followed the inductive-analytical approach by extrapolating the statements of Jurists and legal texts related to the subject of the study, analyzing them, and then devising precautionary measures to prevent travel in jurisprudence and law, through the doctrinal and legal texts contained in the study, and their applications in the Jordanian Sharia courts. The study found that the Sharia courts in Jordan apply the precautionary travel ban procedure within their jurisdiction. The Sharia courts are also taking measures to ensure that the travel ban is not used maliciously. The study recommended the need to continue research on the topic of precautionary measures in general –including travel bans - at the level of Islamic jurisprudence and contemporary laws alike, and the need to continue research on the applications of Jordanian Sharia courts in general, especially concerning the issue of travel bans.